Nerve Transfer Surgery: A Systematic Review of Current Practices, Outcomes, and Future Directions - Muhammad Hagi; Firdath Rubenzani; Fakhrul Hendra; Mulyadi Mulyadi (Eduvest - Journal of Universal Studies, 2026)
Peripheral nerve injuries remain a significant clinical challenge because they can result in permanent motor and sensory dysfunction, reduced independence, and impaired quality of life. Nerve transfer surgery has emerged as an advanced reconstructive approach that redirects functional donor nerves to damaged recipient nerves to restore neurological function. This study aimed to systematically review current practices, clinical outcomes, influencing factors, and future directions of nerve transfer surgery across various neurological conditions. A systematic review method was applied following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant studies were identified from scientific databases, including PubMed, Scopus, ScienceDirect, and Web of Science, based on predefined inclusion and exclusion criteria. The findings indicated that nerve transfer surgery provided significant improvements in motor recovery, sensory restoration, and functional performance, particularly in patients with brachial plexus injuries, spinal cord injuries, facial paralysis, and complex peripheral nerve injuries. However, successful outcomes were strongly influenced by surgical timing, injury severity, donor nerve selection, surgeon expertise, and postoperative rehabilitation. The review also highlighted that objective functional improvements did not always correspond with patient-reported recovery, indicating the need for comprehensive outcome assessments. In conclusion, nerve transfer surgery represents a transformative advancement in peripheral nerve reconstruction; however, further large-scale clinical studies and innovative regenerative strategies are required to optimize long-term functional outcomes and expand its clinical applications.